Lenticular changes in eyes with advanced intraocular retinoblastoma: A histopathological study of 48 enucleated eyes. (19th May 2022) - Jakati, Saumya; Vempuluru, Vijitha S; Mohamed, Ashik; Mishra, Dilip K; Kaliki, Swathi
ABSTRACT: Purpose: To evaluate the lenticular changes in advanced intraocular retinoblastoma (RB) and identify the risk factors for cataract in these eyes. Methods: Retrospective analysis of 48 primary enucleations. Results: All enucleated eyes were classified either as group D (n = 7; 15%) or group E (n = 41; 85%) tumors based on the International Classification of Intraocular Retinoblastoma. Of the 48 enucleated eyes with RB, cataract was noted clinically in only 5 (18%) cases, while histopathology revealed cataractous changes in 28 (58%) cases. Based on histopathology, the cataractous changes included anterior subcapsular cataract ( n = 10; 36%), cortical cataract ( n = 6; 21%), posterior subcapsular cataract ( n = 10; 36%) and both anterior and posterior subcapsular cataract ( n = 2; 7%). Based on multivariate logistic regression, only increased area of necrosis on histopathology was the significant ( p = .009) factor predictive of cataractous changes in lens with an odds ratio of 1.08. Conclusion: Eyes with advanced RB can harbor cataract in 58% cases, though most of these are subclinical. Clinically significant cataract may be evident in only 18% cases. Increased tumor necrosis is associated with the development of cataractous changes in RB cases.